TRANSPORTE DE POLEN POR APIS MELLIFERA EN LA PAMPA DEL TAMARUGAL - Toro, H.; Chiappa, E.; Covarrubias, R.; Villaseñor, R. (Acta Entomológica Chilena, 2022)
Apis mellifera acts as a good potential pollinator of Prosopis tamarugo in the desert part of Chile. Several colonies have been carried over to the Pampa del Tamarugal during the blooming season, in order lo increase the productivity of honey. About 10 per cent of the foragers show full pollen loads, bolh in winter and spring time; almost all of the foragers observed carned pollen on the clypeus and sternal thoracic hairs. Wild colonies were in very poor conditions, presenting no adaptations lo the xeric environment. The floral biology of P. tamarugo shows interesting features thal are betler understood under the Bateman’s Principie.